Controlled Growth of Dichlorogermanium Oligomers from Lewis Basic Hosts1. Issue 25 (27th May 2013) - Al‐Rafia, S. M. Ibrahim; Momeni, Mohammad R.; McDonald, Robert; Ferguson, Michael J.; Brown, Alex; Rivard, Eric
<x xml:space="preserve">Abstract</x> To branch or not to branch: A mild stepwise route to various linear and branched (GeCl2)x oligogermylenes supported by Lewis bases is reported, including the carbene‐bound Ge4 complex NHC⋅GeCl2Ge(GeCl3)2 (see picture). Dipp=2, 6‐iPr2C6H3, NHC=N‐heterocyclic carbene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>